In-Depth Analysis of Contemporary Grayscale Image Dehazing Methods: A Comprehensive Review - M. Baba, Asifa (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Since the fog results in loss and color distortion in an image under poor weather circumstances, an efficient image defogging algorithm is required for retrieving various details in an image and hence recovery of a true color information for visibility improvement. In this paper several state-of-art techniques designed by different researchers towards solving this problem in order to enhance the image by improving the existing present day approaches have been presented. Various enhancements in this area are suggested to increase the value of quality parameters which leads to the better defogged image and hence decreases the road accidents existing day by day. Several intelligent techniques including Q-Deep learning methods with other computer vision algorithms have been suggested to improve upon the visibility of the foggy scene. Finally, the whole review have been concluded by pointing out the several advantages and shortcomings of the existing literature.